2017
DOI: 10.1038/srep42902
|View full text |Cite
|
Sign up to set email alerts
|

Suramin interacts with the positively charged region surrounding the 5-fold axis of the EV-A71 capsid and inhibits multiple enterovirus A

Abstract: Suramin was previously shown to bind to the EV-A71 capsid through its naphthalenetrisulfonic acid groups, thereby reducing virus-cell binding and inhibiting viral replication. Here, we identify VP1-145 as the critical amino acid that accounts for the differential sensitivity of EVA-71 viruses to suramin. A single Q or G to E substitution at VP1-145 results in an approximately 30-fold shift of IC50 or IC90 values reproducing the inhibition profile observed with field isolates expressing either the 145Q or E mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…This is in agreement with other studies that also reported on the inhibition of virus binding or entry by suramin (16,23,27). Several studies have suggested that negatively charged suramin molecules can bind to positive charges on virions (22,28,29). Our data suggest that the antiviral effect of suramin is primarily due to inhibition of an early step in the SARS-CoV-2 replication cycle, and we suspect that this is due to binding of the compound to SARS-CoV-2 virions, interfering with their binding to the cell receptor and possibly also inhibiting fusion.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with other studies that also reported on the inhibition of virus binding or entry by suramin (16,23,27). Several studies have suggested that negatively charged suramin molecules can bind to positive charges on virions (22,28,29). Our data suggest that the antiviral effect of suramin is primarily due to inhibition of an early step in the SARS-CoV-2 replication cycle, and we suspect that this is due to binding of the compound to SARS-CoV-2 virions, interfering with their binding to the cell receptor and possibly also inhibiting fusion.…”
Section: Discussionsupporting
confidence: 93%
“…Analyses of the amino acid changes in the VP1 gene suggested that CV‐A6 had changed its infectivity of the host and contributed to the development of anti‐EV drugs targeting capsid and a vaccine . In the current study, some mutations in the VP1 loops were detected, but this analysis was limited because only VP1 was investigated, despite capsid protein comprising VP1, VP2, and VP3 complexes.…”
Section: Discussionmentioning
confidence: 74%
“…Several clinical and preclinical studies have highlighted the pleiotropic beneficial effects of suramin on other clinical domains (8 -10, 13, 27-30). The discovery that suramin could prevent infection by several important viral pathogens, including Zika virus (12), herpes simplex virus (31), and others (11,13,27) might indicate that it has potential to be applied to treat multiple sexually transmitted infections.…”
Section: Discussionmentioning
confidence: 99%